THE EFFECT OF HIGH PERFORMANCE WORK PRACTICES AND THAI BUDDHIST CULTURE ON JOB EMBEDDEDNESS OF NURSING PROFESSION: THE EVIDENCE OF GOVERNMENT HOSPITAL IN SAMUTSAKHON PROVINCE - นิลเพ็ชร์ ชุติมา; พิริยะกุล ระพีพรรณ (Academic Journal Phranakhon Rajabhat University, 2019)
The nursing career is a career that is sacrificed by hard work. But it is a job that recognizes in Thai society. The previous study focused on the cause of job burnout,while many professional nurses still love and work in this profession until retirement. In this case, often referred to as the embedding of job issue. Therefore leads to our research in the context of the Thai Buddhist culture and the new contemporary of HR Management: High Performance Work Practices as independent factors that effect to job embeddedness with two intermediate factors: mindfulness and self-control. The sample size 400 was sampling from Buddhist professional nurse and works in a public hospital in Samutsakhon province. The study indicated that factors that Thai Buddhist culture has the highest total effect on job embeddedness with 0.72. Moreover, Thai Buddhist culture has positive effects on self-control and mindfulness with highly significant